Upaya Peningkatan Pendapatan dengan Diversifikasi Kerajinan Tangan Bahan Batik Lokal Banyuwangi - Ratnawati R; Yayuk Ngesti Rahayu; M Taufiq Noor Rokhman (Idea Pengabdian Masyarakat, 2022)
Batik is an Indonesian cultural heritage that must be maintained and developed, besides the development of batik craftsmen with motifs that show regional characteristics is one of the sources of income for craftsmen. Diversification of batik cloth products is a strategy to increase their sales and income.The purpose of this community service activity is to provide solutions to the problems of batik craftsmen in Banyuwangi Regency with a touch of creativity by diversifying products (handmade) based on local batik produced in addition to batik cloth and clothes (elephant oling, broken coffee, kangkung bundles, gedheg and so on). Several efforts have been made to increase production such as souvenirs, wallets, bags, tissue holders and several other products. Activities carried out in service include training in production, marketing and packaging practices at Batik Banyuwangi craftsmen. Product diversification is carried out by improving production processes, strengthening business through packaging of diversified products, training in the diversification process to produce handicraft products (bags, wallets, sandals, Banyuwangi udeng).